Capacitance and conductance characterization of nano-ZnGa2Te4/n-Si diode - Fouad, S. S.; Sakr, G. B.; Yahia, I. S.; Abdel-Basset, D. M.; Yakuphanoğlu, Fahrettin (Pergamon-Elsevier Science Ltd, 2014)
Capacitance-voltage (C-V) and conductance-voltage (G-V) characteristics of p-ZnGa2Te4/n-Si HJD were studied over a wide frequency and temperature. Both the interface states density N-ss and series resistance R-s were strongly frequency and temperature dependent. The interface states density N-ss is decreased with increasing frequency and increase with increasing temperature. The values of the built-in potential (V-bi) were calculated and found to increase with increasing temperature and frequency. The values of capacitance C, conductance G, series resistance R-s, corrected capacitance C-ADJ, corrected conductance G(ADJ), dielectric constant (epsilon'), dielectric loss (epsilon ''), loss tangent (tan delta) and the AC conductivity (sigma(ac)) are strongly dependent on the applied frequency, voltage and temperature. The obtained results show that the locations of N-ss and R-s have a significant effect on the electrical characteristics of the studied diode. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Semiconductors; Vapor deposition; Atomic force microscopy; Impedance spectroscopy; Dielectric properties